Optimization of MRI measurements of calf muscle atrophy following acute Achilles tendon rupture - El Haddouchi, Ibrahim; Brøgger Overgaard, Anders; Swennergren Hansen, Maria; Hølmich, Per; Weisskirchner Barfod, Kristoffer (Journal of the Foot & Ankle, 2025)
Objective: Investigate whether single slice cross- sectional area (CSA) measurement could be used as a surrogate for volumetric measurement on magnetic resonance imaging (MRI) in evaluating calf muscle atrophy after Achilles tendon rupture (ATR). We hypothesized that atrophy estimated by single slice CSA measurement had an R-squared (R2) value above 0.7 when compared to volumetric measurements. Methods: This was a cross-sectional study of patients one year after ATR. An MRI of both calves was performed. Muscle volume was calculated by measuring CSA of the muscles of the triceps surae and the deep flexors on axial slices every 2 cm. The limb symmetry index (LSI) was used to estimate atrophy. The two methods for assessing atrophy, single slice CSA and volumetric measurement, were compared by fitting a linear regression model and calculating the R2-value. Results: The strongest correlation was obtained when measuring CSA of the triceps surae (R2 = 0.780), soleus (R2 = 0.636), medial gastrocnemius (R2 = 0.612) and lateral gastrocnemius (R2 = 0.556) 26 cm above talus, and the deep flexors (R2 = 0.493) 14 cm above talus. Conclusions: Cross- sectional area measurement on a single MRI slice can be applied as a surrogate for volumetric measurements when investigating atrophy of the triceps surae muscle group as a whole. However, this approach is not suitable when investigating the individual parts of the muscle. Level of evidence III, Cross-sectional comparative study.